Strongyloidiasis Epidemiology and Treatment Response in Patients with HIV Infection. (4th October 2017) - Cortes-Penfield, Nicolas; Moore, Cody; Arduino, Roberto; Serpa, Jose
Abstract: Background: We sought to characterize the epidemiology of HIV and S. stercoralis coinfection in an urban HIV cohort, and to investigate the effect of S. stercoralis infection on HIV virologic control and immune recovery. Methods: We reviewed the medical records of all HIV-infected patients diagnosed with strongyloidiasis who received care at Thomas Street Health Center (Houston, TX) between 2000 and 2015. For each case we included up to two matched HIV-infected patients without strongyloidiasis (controls). Matching was based on age, sex, ethnicity, baseline CD4 percentage, and HIV viral load at the time of strongyloidiasis diagnosis in the case patient. We recorded patient demographics, comorbidities, CD4 count and percentage, HIV viral load, and absolute eosinophilia count (AEC) at the time of HIV diagnosis, strongyloidiasis diagnosis, and six and twelve months after ivermectin treatment. Results: We identified 15 cases of HIV and S.stercoralis coinfection; 13 had at least one available matched control. The mean age of coinfected patients was 45; all were Hispanic, 84.6% were male, and the mean CD4 nadir was 146 cells/ul. At the time of strongyloidiasis diagnosis, the mean CD4 count was 460 cells/ul, HIV RNA viral load 2.07 logs/ml, and AEC was 1, 360 cells/μL. At 6 and 12 months after treatment, CD4 counts were 514 and 464 cells/μL, HIV RNA viral loads 1.78 and 2.31 log/mL, and AECs 319 and 362 cells/μL, respectively. Although CD4 counts increased 6 months after treatment, they returned to baseline levels at 12 months; neither change achieved statistical significance. The reduction in AECs after ivermectin treatment was statistically significant ( P < 0.001). Matched controls without S.stercoralis had lower AECs at baseline, 6 months, and 12 months; otherwise, there were no differences between cases and controls. Conclusion: Strongyloidiasis treatment in HIV-infected patients led to normalization of the AEC at 6 months in most cases, but AECs remained higher than in control patients. Persistently elevated AECs may suggest treatment failure or reinfection. Our study was unable to identify any effect of S. stercoralis infection or treatment on HIV virologic suppression or immunologic recovery; larger studies are warranted to investigate the effect of strongyloidiasis on HIV disease. Disclosures: All authors: No reported disclosures.